2021
DOI: 10.22219/satwika.v5i2.18019
|View full text |Cite
|
Sign up to set email alerts
|

Arketipe peran Ibu dalam cerita rakyat nusantara dan kontribusinya terhadap terapi lintas budaya

Abstract: Saat ini, sensivitas budaya di bidang psikoterapi menjadi isu yang penting karena tumbuhnya kesadaran bahwa berbagai praktik yang dilakukan selama ini bersifat Eurosentris. Para ahli mengabaikan fakta keberagaman latar belakang budaya pasien. Padahal, banyak terapis yang menangani pasien dari berbagai latar belakang budaya menyadari adanya keunikan budaya pada setiap pasiennya. Sayangnya, belum banyak riset yang berusaha memahami dan menggali kekayaan budaya yang ada dalam cerita rakyat dan dimanfaatkan dalam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Folktales is also used as a means of passing on values between generations (Andalas & Qur'ani, 2019). Folktales contains the values, ideas, and worldviews of the people who own the stories (Andalas, 2017(Andalas, , 2018Dundes, 1969). As a medium for transmitting knowledge and values, folktales should not only be considered as a means of inheritance but the content of folktales should be assessed within the framework of education.…”
Section: Resultsmentioning
confidence: 99%
“…Folktales is also used as a means of passing on values between generations (Andalas & Qur'ani, 2019). Folktales contains the values, ideas, and worldviews of the people who own the stories (Andalas, 2017(Andalas, , 2018Dundes, 1969). As a medium for transmitting knowledge and values, folktales should not only be considered as a means of inheritance but the content of folktales should be assessed within the framework of education.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, research entitled "Arketipe Peran ibu dalam Cerita Rakyat Nusantara dan Kontribusinya dalam Terapi Lintas Budaya" by Andalas and Sugiarti raises the role of a mother from a different perspective. This research explores the archetype of the mother's role in Nusantara folklore, its significance as a cultural mentality of society, and the extent of its contribution to cross-cultural therapy (Andalas & Sugiarti, 2021). The research exploring 288 Indonesian folk tales found that the archetype of the mother's role was formed into three characters: a good mother, a bad mother, and a transformed mother.…”
Section: B Literature Reviewmentioning
confidence: 99%
“…The protagonist's mother becomes an antagonist caused of the child's disobedience or the presence of a third party. The descriptions of the three archetypes of the mother's role show the role of the mother in everyday life and can be utilized in the field of therapy (Andalas & Sugiarti, 2021).…”
Section: B Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation